Vaccination coverage survey and seroprevalence among forcibly displaced Rohingya children, Cox's Bazar, Bangladesh, 2018: A cross-sectional study. - Leora R Feldstein; Sarah D Bennett; Concepcion F Estivariz; Gretchen M Cooley; Lauren Weil; Mallick Masum Billah; M Salim Uzzaman; Rajendra Bohara; Maya Vandenent; Jucy Merina Adhikari; Eva Leidman; Mainul Hasan; et al. (PLoS Medicine)
Background During August 2017-January 2018, more than 700,000 forcibly displaced Rohingyas crossed into Cox's Bazar, Bangladesh. In response to measles and diphtheria cases, first documented in September and November 2017, respectively, vaccination campaigns targeting children <15 years old were mobilized during September 2017-March 2018. However, in a rapidly evolving emergency situation, poor sanitation, malnutrition, overcrowding, and lack of access to safe water and healthcare can increase susceptibility to infectious diseases, particularly among children. We aimed to estimate population immunity to vaccine-preventable diseases (VPDs) after vaccination activities in the camps to identify any remaining immunity gaps among Rohingya children. Methods and findings We conducted a cross-sectional serologic and vaccination coverage survey in Nayapara Registered Refugee Camp ("Nayapara") and makeshift settlements (MSs) April 28, 2018 to May 31, 2018, among 930 children aged 6 months to 14 years. MSs are informal, self-settled areas with a population of more than 850,000, the majority of whom arrived after August 2017, whereas Nayapara is a registered camp and has better infrastructure than MSs, including provision of routine immunization services. Households were identified using simple random sampling (SRS) in Nayapara and multistage cluster sampling in MSs (because household lists were unavailable). Dried blood spots (DBSs) were collected to estimate seroprotection against measles, rubella, diphtheria, and tetanus, using Luminex multiplex bead assay (MBA). Caregiver interviews assessed vaccination campaign participation using vaccination card or recall. In Nayapara, 273 children aged 1 to 6 years participated; 46% were female and 88% were registered refugees. In MSs, 358 children aged 1 to 6 years and 299 children aged 7 to 14 years participated; 48% of all children in MSs were female, and none were registered refugees. In Nayapara, estimated seroprotection among 1- to 6-year-olds was high for measles, rubella, diphtheria, and tetanus (91%-98%; 95% confidence interval [CI] 87%-99%); children >6 years were not assessed. In MSs, measles seroprotection was similarly high among 1- to 6-year-olds and 7- to 14-year-olds (91% [95% CI 86%-94%] and 99% [95% CI 96%-100%], respectively, p < 0.001). Rubella and diphtheria seroprotection in MSs were significantly lower among 1- to 6-year-olds (84% [95% CI 79%-88%] and 63% [95% CI 56%-70%]) compared to 7- to 14-year-olds (96% [95% CI 90%-98%] and 77% [95% CI 69%-84%]) (p < 0.001). Tetanus seroprevalence was similar among 1- to 6-year-olds and 7- to 14-year-olds (76% [95% CI 69%-81%] and 84% [95% CI 77%-89%], respectively; p = 0.07). Vaccination campaign coverage was consistent with seroprotection in both camps. However, nonresponse, the main limitation of the study, may have biased the seroprotection and campaign coverage results. Conclusions In this study, we observed that despite multiple vaccination campaigns, immunity gaps exist among children in MSs, particularly for diphtheria, which requires serial vaccinations to achieve maximum protection. Therefore, an additional tetanus-diphtheria campaign may be warranted in MSs to address these remaining immunity gaps. Rapid scale-up and strengthening of routine immunization services to reach children and to deliver missed doses to older children is also critically needed to close immunity gaps and prevent future outbreaks.